Comparison of the Success of Guava Stem Cuttings (Psidium guajava) Using the Chemical Liquinox Start (Vitamin B1), Root Up, and Natural Ingredients of Red Onion (Allium cepa L) - Ridwansyah Munthe; Hilwa Walida; Dini Hariyati Adam; Khairul Rizal (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Guava (Psidium guajava L.) is a tropical plant that holds significant popularity and economic value in Indonesia. Despite its benefits, many Indonesians still face challenges in successfully cultivating guava seeds. Traditionally, guavas are propagated from seeds, which often results in lower-quality fruit. Seed-grown trees may take longer to bear fruit, and the fruit produced may not resemble that of the parent plant. This study aims to evaluate the success rate of guava propagation using stem cuttings treated with two different chemicals—Root Up and Liquinox Start—as well as a natural alternative, shallot extract. The cuttings were treated uniformly across all treatments, and the growth parameters observed included the number of shoots, the number of leaves, and the length of the shoots over two months from April 20 to June 22, 2025. The results indicated a significant difference between the three treatments. Root Up treatment produced the longest shoot growth on average, while Liquinox Start also showed a relatively high rate of shoot development. Shallot extract, a natural alternative, also yielded promising results, offering an environmentally friendly and easily accessible option for guava propagation. While chemical treatments, such as Root Up, led to optimal results in terms of shoot, leaf, and shoot length development, the use of shallots demonstrates that natural ingredients can also provide a sustainable and effective approach to guava propagation. Based on the findings, Root Up is recommended for accelerating guava plant growth, but shallot extract presents a viable, eco-friendly alternative.